Monogeneans (Dactylogyridae) parasitizing gills of Salminus hilarii from a Neotropical reservoir, Brazil - Brandao, Heleno [UNESP]; Yamada, Fabio Hideki [UNESP]; Toledo, Gislayne de Melo [UNESP]; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo Jose da [UNESP] (Brazilian Coll Veterinary Parasitology, 2013)
With the aim of creating an inventory of the metazoan gill parasites of Salminus hilarii in the Taquari River, state of Sao Paulo, Brazil, five species of monogeneans (Anacanthorus contortus, A. bicuspidatus, Annulotrematoides parisellei, Jainus iocensis and Tereancistrum arcuatus) are reported the first time for this host. A total of 28 fish were sampled quarterly between April 2011 and January 2012, with 10 hosts in a lentic ecosystem and 18 in a lotic ecosystem. Quantitative ecological descriptors (prevalence, intensity of infestation and abundance) were calculated for the purpose to comparing the two ecosystems sampled (lentic and lotic ecosystems). However, no quantitative difference between the lentic and lotic ecosystems was observed. The present study has made available a checklist for species of the genus Anacanthorus and their hosts and geographical distribution in the Neotropical region up to the present time.
Keywords: Ectoparasite; Monogenea; freshwater fish; Taquari River